Indonesian hydro energy potential map with run-off river system. Issue 1 (November 2021) - Pranoto, B; Soekarno, H; Cendrawati, D G; Akrom, I F; Irsyad, M I A; Hesty, N W; Aminuddin,; Adilla, I; Putriyana, L; Ladiba, A F; Widhiatmaka,; Darmawan, R; et al.
Abstract: Indonesia aims to decarbonize the energy sector by accelerating the use of new and renewable energy, expected to reach 31% of total energy supply in 2050. One of important tools to achieve the target is renewable energy potential maps including hydro energy potential maps. Yet, existing hydro energy potential maps have several weaknesses such as sites coordinate not on the river network. This study aims to update and to improve the run-off river system energy hydro maps by using a novel method considering multiple factors that are head values, discharge river, gravity, and the efficiency of the hydro system. In calculating the head value, we use DEM data from SRTM 1 arc second to estimate difference between upstream and downstream elevations. We also did Q90 modeling using WFLOW software as generate the discharge value. In the end, we verified the maps by using field measurement data in 776 sites from previous study. As a result, we estimate the total potential of hydro energy with the run-off river system in Indonesia reaches 94, 627 MW distributed in 52, 566 sites.